Determination of the Some Results for Coupled Fixed Point Theory in C*-Algebra Valued Metric Spaces - omran, saleh; Ã–ZER, Ã–zen (IndoMS, 2020)
In the present paper, we introduce the coupled xed point theorem in C*-algebra valued metric spaces. We get a C*-algebra valued metric space which get values in noncomutative operators. We demonstrate existance and uniqeness of coupled fixed point in a such space. Besides, we support our results by giving numerical examples.